2002
DOI: 10.1021/jo020487p
|View full text |Cite
|
Sign up to set email alerts
|

Haouamines A and B:  A New Class of Alkaloids from the Ascidian Aplidium haouarianum

Abstract: The chemical study of the ascidian Aplidium haouarianum has led to the isolation of the new metabolites haouamines A (1) and B (2) which belong to a novel class of alkaloids. The structure of 1 was established by interpretation of its spectroscopic data and those of the N-methyl derivative 3, and confirmed by X-ray crystallographic analysis. The structure of 2 was deduced by spectroscopic study of its peracetyl derivative 2a. In solution each haouamine exists as an unseparable mixture of two interconverting is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
108
1
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(118 citation statements)
references
References 15 publications
7
108
1
2
Order By: Relevance
“…The discovery of Haouamine A (Figure 14, Compound 64) from a species of ascidian (sea squirt) 104 provided a unique molecular structure following extensive NMR analysis and X-ray crystallography. This structure contained a p-cyclophane moiety, a biaryl axis with a relatively unique, highly strained 'bent' benzene ring, 105 and a spiro fused-ring system.…”
Section: Haouamine A: Natural Atropisomeric Alkaloid With a Complex Smentioning
confidence: 99%
See 1 more Smart Citation
“…The discovery of Haouamine A (Figure 14, Compound 64) from a species of ascidian (sea squirt) 104 provided a unique molecular structure following extensive NMR analysis and X-ray crystallography. This structure contained a p-cyclophane moiety, a biaryl axis with a relatively unique, highly strained 'bent' benzene ring, 105 and a spiro fused-ring system.…”
Section: Haouamine A: Natural Atropisomeric Alkaloid With a Complex Smentioning
confidence: 99%
“…The originally isolated molecule was observed to contain two rapidly-interconverting isomers; the cause for this was thought to be the result of either a slowed pyramidal inversion of the sp 3 nitrogen, or the presence of an atropisomer (Figure 14, compound 19). 104 Computational modelling studies indicated a pyrimidal nitrogen inversion to be the more likely cause of this interconversion, however to confirm the configurational stability of the biaryl axis, an atropselective total synthesis had to be devised, which was eventually realised by Baran et al 106 Figure 13: The structure of Haouamine A (64) and its atropisomer (65), with the highly uncommon distorted benzene ring shown in blue.…”
Section: Haouamine A: Natural Atropisomeric Alkaloid With a Complex Smentioning
confidence: 99%
“…With key intermediate 59 in hand, the asymmetric synthesis of kainoid 60 was accomplished via a high-yielding sequence. The synthesis of iso-haouamine B is another example (Scheme 13) [39,40]. Structurally, this alkaloid, 64, consists of an indeno-tetrahydropyridine core fused to a highly distinctive 11-membered p-cyclophane ring.…”
Section: Chiral Pool: Serinementioning
confidence: 99%
“…) [1] kindly provided by Professor Zubía which showed that the unnatural enantiomer had been synthesized and thus proving the configuration of natural haouamine A to be 8:9R,17S,26S.…”
mentioning
confidence: 99%